QUALITY AND QUANTITY OF FRESH SEMEN OF BALI BULL AT BATURITI INSEMINATION CENTER - N. M. L. E., Witarja; Ardika, I N.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 8 No 1 (2020): Issue 8 No. 1 (2020); January - April, 2020)
This study was conducted at the Baturiti Artificial Insemination Center. The purpose of this study was to determine the quality of fresh semen and frozen semen production of Bali Bull at UPT BIBD Baturiti. The material used in this study is the record of semen production consisting of the quality of fresh semen and the amount of frozen semen straw from 9 Bali cattle. The method used was a technical survey, interview, and on the job training, and was obtained through the record of the collection of fresh semen in the Balinese Bull during October 2019 in the Technical Implementation Unit (UPT) of the Artificial Insemination Center Baturiti. Variables observed included semen volume, color, percentage of individual motility, spermatozoa concentration, and amount of frozen semen production. PKM results indicate that the average quality of fresh semen of Bali bull in UPT BIBD Baturiti in October 2019 consisted of semen volume of 6.01 ml, color of beige, percentage of individual motility of 70%, and spermatozoa concentration of 1,072 million/ml. The conclusion of this PKM is that in general the quality and quantity of fresh semen of bali cattle in UPT BIBD Baturiti includes semen volume, color, percentage of individual motility, and spermatozoa concentration in accordance with the standard. Keywords: frozen semen, motility, concentration, cement volume, bali bull